Peranan Kepolisian Republik Indonesia dalam Menanggulangi Peredaran Minuman Beralkohol secara Ilegal - Bhirawa Surya Kentana; Enny Ristanti; Sita Agustina Siahaan (Bhirawa Law Journal, 2022)
Liquor or better known as alcoholic beverage is a drink that contains ethanol (ethyl alcohol). The main factor for the increase in alcoholic beverages below quality standards is because there is a price divider and the quality of consumer demand. Home-scale beverage manufacturers take this opportunity by providing products that are of questionable safety. For consumers, the availability of alcoholic beverages at low prices encourages consumption without considering product quality standards. This is the background of the research entitled The Role of the Indonesian Police in Combating the Illegal Circulation of Alcoholic Drinks. This study has a problem formulation regarding efforts to overcome the illegal circulation of liquor in the city of Malang. The types of data used to examine this research are primary data and secondary data. Based on the analysis of the data, it was found that the Malang City Police took preventive and repressive efforts and found several inhibiting factors in tackling the illegal circulation of alcoholic beverages.